Desain Interkoneksi Bioreaktor Sampah Padat Perkotaan Dengan Model Sirkulasi Air Lindi Anaerob Untuk Meningkatkan Produksi Gas Methane - Zamzami Septiropa (Jurnal Gamma, 2012)
Desain Interkoneksi Bioreaktor Sampah Padat Perkotaan Dengan Model Sirkulasi Air Lindi Anaerob Untuk Meningkatkan Produksi Gas MethaneZamzami SeptiropaStaf Pengajar Jurusan Teknik Sipil , Fakultas TeknikUniversitas Muhammadiyah Malang,e-mail : zamseptiropa@umm.ac.idABSTRACTThe existence of gravity of the pressing weight of its own garbage heap of garbage will be squeezed to make trash (pressing) and out of the leachate (Leachate). Contained in the waste leachate has elements glokosa (C6H12O6), Amino Acid and Ammonia (NH3), which will help the growth of anaerobic bacteria that produce methane (CH4) and carbon diaoksida (CO2). Humidity will be reduced as the discharge of garbage in garbage leachate resulting decline in productivity of anaerobic bacteria, thus maintaining levels of humidity (moisture content) is very important in stabilizing the productivity of anaerobic bacteria.In the humidity of 59.85% productivity waste anaerobic bacteria produce landfill gas in stagnant in the range of less than 10% CH4. With a circulation process of garbage leachate to maintain moisture of 67.25% are able to stabilize the production of landfill gases, especially CH4 concentration more than 25%. Leachate circulation periodically able to stabilize the moisture content of waste, from which the waste water content, it makes the productivity of stable anaerobic bacteria produce methane gas in concentrations between 20% -25% is quite a power plant of energy.Renewable energy was from waste to be more realistic to be implemented in full scale in place of final processing (TPA) / Landfill. So the need for energy for the benefit of the power plant could help meet the electricity needs of the community.Keywords: bioreactor anaerobic, leachate circulation